2019
DOI: 10.1007/s10560-018-0594-9
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Behavioral Problems and Psychosocial Skills in Adolescents in Residential Care

Abstract: Research suggests that mental health problems in adolescents in residential care (RC) are more prevalent than for youth in the community, and that psychosocial competencies are protective factors of mental health. This study compared adolescents in RC in Portugal, with a Portuguese community sample on the incidence of mental health problems and psychosocial skills, explored gender differences and the relationships between mental health problems and psychosocial competencies. Four hundred and forty-three adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 31 publications
4
21
1
4
Order By: Relevance
“…In line with other research, the interpersonal relationships among adolescents, as well as with carers and teachers, are especially important to these children and positively correlate with their subjective wellbeing (e.g., Delgado et al 2019;Pérez-García et al 2019). Moreover, Campos et al (2019) have shown that participation in clubs, contact with siblings, parents and other significant adults are negatively, and significantly, correlated to several mental-health problems (e.g., depression, anxiety, aggressive behaviour, etc.). Having said that, contact with birth families was very important for children in this study: in general terms, even when living in alternative care, it made them feel good, although at the same time many of them were able to identify the negative impact of family related issues or bad experiences in the past, and some of them preferred to avoid contact entirely.…”
Section: Discussionmentioning
confidence: 99%
“…In line with other research, the interpersonal relationships among adolescents, as well as with carers and teachers, are especially important to these children and positively correlate with their subjective wellbeing (e.g., Delgado et al 2019;Pérez-García et al 2019). Moreover, Campos et al (2019) have shown that participation in clubs, contact with siblings, parents and other significant adults are negatively, and significantly, correlated to several mental-health problems (e.g., depression, anxiety, aggressive behaviour, etc.). Having said that, contact with birth families was very important for children in this study: in general terms, even when living in alternative care, it made them feel good, although at the same time many of them were able to identify the negative impact of family related issues or bad experiences in the past, and some of them preferred to avoid contact entirely.…”
Section: Discussionmentioning
confidence: 99%
“…We found that adolescent psychosocial skills were the most dominant factor associated with EBP. A similar study was conducted to Portuguese adolescents showed that psychosocial skills were negatively correlated with EBPs [26]. Psychological skills can be increased of psychological well-being.…”
Section: Discussionmentioning
confidence: 66%
“…Studies have consistently identified that youth in residential care have more mental health problems and psychopathology than the general population. Even though only a relatively small proportion of this population presents clinically evaluated and diagnosed behavioral and mental health problems in Portugal ( ISS.IP, 2020 ), children and youth in care are, nonetheless, a high-risk population in terms of their mental health, namely, externalizing and internalizing problems (e.g., Gearing et al, 2014 ; González-García et al, 2017 ; Magalhães and Calheiros, 2017 ; Campos et al, 2019 ). They present a relatively high prevalence of conduct disorder, attention-deficit hyperactivity disorder, depression, post-traumatic stress disorder, and generalized anxiety disorder ( Heflinger et al, 2000 ; Tarren-Sweeney and Vetere, 2013 ; Rodríguez et al, 2015 ; Jozefiak et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%